Antibiotic administration within 1 hour for open lower extremity fractures is not associated with decreased risk of infection. Issue 2 (8th February 2023) - Grigorian, Areg; Schellenberg, Morgan; Inaba, Kenji; Martin, Matthew; Matsushima, Kazuhide; Lekawa, Michael; Nahmias, Jeffry
Abstract : Contrary to previous reports the rate of surgical site infection after open femur/tibia fractures is not only rare but was not found to be associated with the timing of antibiotic administration. Abstract : BACKGROUND: Open fractures have a high risk of infection with limited data correlating timing of prophylactic antibiotic administration and rate of subsequent infection. The Trauma Quality Improvement Program has established a standard of antibiotic administration within 1 hour of arrival, but there is a lack of adequately powered studies validating this quality metric. We hypothesize that open femur and/or tibia fracture patients undergoing orthopedic surgery have a decreased risk of infectious complications (osteomyelitis, deep and superficial surgical site infection) if antibiotics are administered within 1 hour of presentation compared with administration after 1 hour. METHODS: The 2019 Trauma Quality Improvement Program was queried for adults with isolated (Abbreviated Injury Scale <1 for the head/face/spine/chest/abdomen/upper extremity) open femur and/or tibia fractures undergoing orthopedic surgery. Transfer patients were excluded. Patients receiving early antibiotics (EA) within 1 hour were compared with patients receiving delayed antibiotics (DA) greater than 1 hour from arrival. RESULTS: Of 3, 367 patients identified, 2, 400 (70.4%) received EA. Patients receiving EA had a higher rate of infections compared with DA (1.1% vs. 0.2%, p = 0.011). After adjusting for age, comorbidities, injury severity, nerve/vascular trauma to the lower extremity, washout of the femur/tibia performed in <6 hours, blood transfusion, and admission vitals, patients in the EA group had a similar associated risk of surgical site infection/osteomyelitis compared with the DA cohort ( p = 0.087). These results remained in subset analyses of patients with only femur, only tibia, and combined femur/tibia open fractures (all p > 0.05). CONCLUSION: In this large national analysis, approximately 70% of isolated open femur or tibia fracture patients undergoing surgery received antibiotics within 1 hour. After adjusting for known risk factors of infection, there was no association between timing of antibiotic administration and infection. Reconsideration of the quality metric of antibiotic administration within 1 hour for open fractures appears warranted. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level IV. Abstract :